Lire le paysage dans les atlas français : quelques éléments de réflexion - Vincent Veschambre (Projets de Paysage)
Based on a corpus of atlases published in France from 1989, this paper analyses several general trends related to the development and the evolution of regional atlas, in parallel to the decentralization process. During the last ten years, thematic specialization has been operated on these territory atlases, in which the landscape has become one of the most mentioned subjects, through the expression : landscape atlas, (often available on line). Conceived as main piece of the landscape policy, in reference to the European landscape Convention, these landscape atlases cover today most of the national territory. The Landscape is today a more important issue than the notion of heritage even if it remains quite important in the content of these atlases.